Recent Advancements in Metallic Glasses - Khonik, Vitaly A. (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
The Special Issue "Recent Advancements in Metallic Glasses" presents ten original papers, considering both scientific and application issues related to metallic glasses. The papers are devoted to general consideration of the formation and defects of the glassy structure, defect evolution due to heat treatment, deformation behavior upon compression and high-pressure torsion, amorphous-crystalline transformation, hydrogenation behavior, and biomedical applications.